Contextualizing the tone of the operating room in practice: drawing on the literature to connect the dots - Lia, Hillary; Hammond Mobilio, Melanie; Rudzicz, Frank; Moulton, Carol-anne (Frontiers in Psychology, 2023)
The study of teamwork in the operating room has made significant strides in uncovering key constructs which shape safe and effective intraoperative care. However, in recent years, there have been calls to understand teamwork in the operating room more fully by embracing the complexity of the intraoperative environment. We propose the construct of tone as a useful lens through which to understand intraoperative teamwork. In this article, we review the literature on culture, shared mental models, and psychological safety, linking each to the construct of tone. By identifying tone as a theoretical orientation to demonstrate the overlap between these concepts, we aim to provide a starting point for new ways to understand intraoperative team dynamics.